1999
DOI: 10.1007/pl00002582
|View full text |Cite
|
Sign up to set email alerts
|

Fremdkörpergranulom des Pankreaskopfes durch eine Fischgräte – eine sehr seltene Differentialdiagnose des Pankreaskopftumors

Abstract: Despite highly developed scanning methods there is no absolute certainty of delineating malignant pancreatic tumor from chronic pancreatitis. Pancreatitis caused by foreign bodies has occasionally been mentioned in literature. Our report is on the first case of a foreign body granuloma of the pancreatic head caused by a fish-bone transduodenally perforating the pancreas. On preoperative CT and ultrasound as well as by intraoperative inspection and palpation the lesion appeared malignant, so we saw the indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Furthermore, deep penetration into the pancreatic parenchyma would likely result in injury to the main or peripheral pancreatic ducts, leading to acute pancreatitis or potentially causing obstruction of the main pancreatic duct, which could result in chronic pancreatitis or atrophy of the pancreatic tail. Dissection of adjacent small or large vessels would also be anticipated, potentially leading to retroperitoneal hemorrhage 54,65 . In some cases, such severe vascular injury can even be fatal 59 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, deep penetration into the pancreatic parenchyma would likely result in injury to the main or peripheral pancreatic ducts, leading to acute pancreatitis or potentially causing obstruction of the main pancreatic duct, which could result in chronic pancreatitis or atrophy of the pancreatic tail. Dissection of adjacent small or large vessels would also be anticipated, potentially leading to retroperitoneal hemorrhage 54,65 . In some cases, such severe vascular injury can even be fatal 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that around 1% of swallowed foreign bodies penetrate the gastric and duodenal wall, traveling within the abdominal cavity and potentially reaching the liver, pancreas, spleen or even further into the thoracic cavity. 28,33 Our literature review revealed 41 cases of intrapancreatic foreign bodies (Table 3), including 14 suture needles, [23][24][25][26][27][28][29][30][31] 4 metal wires, [32][33][34][35] 19 fish bones, 7,[36][37][38][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54] 2 other pointed bones 55,56, and 2 toothpicks. 57,58 All these foreign bodies are believed to have migrated from the stomach or the duodenum.…”
Section: Hypothesis Of Earlier Ingestionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, abdominal foreign bodies become fiber-wrapped due to inflammation caused by the formation of lumps, and misdiagnosis is not uncommon [ 10 ]. Items such as legacy gauze [ 11 ], surgical sutures [ 12 ], and fish and chicken bones penetrating into the abdominal cavity [ 13 , 14 ] have formed tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur wird ein Fremdkörpergranulom als Ursache eines Pankreaskopftumors beschrieben [9]. Im eigenen Krankengut führte eine Strahlenfibrose der Bauchspeicheldrüse zur operativen Exploration.…”
Section: Einteilung Der Pankreasneoplasienunclassified